Chemotherapy Use in Elderly Patients with Soft Tissue Sarcoma: A Population-based Study. (4th February 2013) - Matushansky, Igor; Dela Cruz, Filemon; Insel, Beverly J.; Hershman, Dawn L.; Neugut, Alfred I.
<x xml:space="preserve">Abstract</x> Adjuvant chemotherapy for soft tissue sarcoma (STS) remains controversial while improvement in survival has never been conclusively demonstrated for metastatic STS. We identified individuals in SEER–Medicare with resected or metastatic STS, 1991–2007. Of 2, 382 patients with resected STS, 106 (4.5%) received chemotherapy. High tumor grade, larger tumor size, and malignant fibrous histiocytoma subtype were associated with chemotherapy receipt. Of 365 patients with metastatic STS, 118 (32.4%) received chemotherapy. Younger age, fewer comorbidities, and being married were associated with chemotherapy receipt. Consistent with clinical trials, we found minimal use of chemotherapy. Clinical factors were associated with chemotherapy receipt in nonmetastatic STS.